Changes of functional components, organic acid, antioxidant activity of heathy vinegar during the aging and its correlation analysis - HU Kun, LIANG Kai, LANG Fanfan, WANG Li, ZHOU Jingli, YAN Yufeng (Zhongguo niangzao)
According to the traditional brewing process of Shanxi aged vinegar, the health vinegars, Dangshen+Huangqi vinegar and Kuqiao+Duzhongye vinegar were prepared by adding Codonopsis pilosula, Astragali radix, Fagopyrum tataricum, Eucommia ulmoides leaves in the acetic acid fermentation stage and then aging for 6 months. The changes of antioxidant activity in vitro, functional components and organic acids contents during aging process were studied, the correlation between functional components, organic acids and antioxidant activity were analyzed, and principal component analysis (PCA) was performed based on the detection results. The results showed that the scavenging rates of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid (ABTS) total antioxidant capacity and Ferric ion reducing antioxidant power (FRAP) of vinegars increased with the aging time, and the contents of functional components and organic acids increased with aging gradually, and the contents of functional components and organic acids also increased gradually. The correlation analysis results showed that the antioxidant activity of Dangshen+Huangqi vinegar was significantly correlated with total flavonoids, total polyphenols, total saponins, oxalic acid and succinic acid (P<0.05), and the total saponins contributed significantly to the antioxidant activity, and the correlation coefficients with DPPH, ABTS and FRAP were 0.752, 0.711 and 0.775, respectively. The antioxidant activity of Kuqiao+Duzhongye vinegar was significantly correlated with total flavonoids, total polyphenols, chlorogenic acid and succinic acid (P<0.05), among them, chlorogenic acid contributed the most to the antioxidant activity, and the correlation coefficients with DPPH, ABTS and FRAP were 0.711, 0.694 and 0.736, respectively. PCA could effectively distinguish the two kinds of healthy vinegar.